Isolation, Characterization, and Application of Bacteriophage for Salmonella Control in Broiler Chickens - Wisanu Wanasawaeng; Thotsapol Thomrongsuwannakij; Niwat Chansiripornchai (Veterinary Medicine International)
The present study explores alternatives to antibiotics for poultry farms. The aims of this study were to isolate and characterize bacteriophages for selection of the appropriate phage, reduce Salmonella in the gastrointestinal tract of broiler chickens, and observe gut microbiota alterations after bacteriophage treatments. In this study, bacteriophages were isolated from two broiler chicken farms, two poultry processing plants, a goat farm, and a pig farm in the central region of Thailand. Out of the 33 samples analyzed, 25 (75.5%) tested positive for the presence of Salmonella bacteriophages. Among the 63 isolates examined, SEpBS-1 was selected for its ability to infect five Salmonella serovars: S. Enteritidis, S. Hadar, S. Typhimurium, S. Dublin, and S. Poona. Thermal stability test of phages showed that phages were stable at −6.5°C–50°C for 30 min, and significantly decreased (p<0.05) at 60°C, and drastically decreased at 70°C. Furthermore, pH stability test of phages showed that phages were stable at pH 5-9. Phage SEpBS-1 was stable in acidic conditions. Phage titers decreased with increased salinity. The morphological characterization of the phage using transmission electron microscopy (TEM) revealed icosahedral heads and thin, long, noncontractile, flexible tails. The phage SEpBS-1 was classified as a member of the Siphoviridae family. The growth curve of the bacteriophage revealed that phage SEpBS-1 for SE had a latent period of 2 h, burst time of 2–3.5 h, and burst size of 166 PFU/infected cell. Phage SEpBS-1 for S. Typhimurium had a latent period of 2.5 h, burst time of 2.5–4 h, and burst size of 973 PFU/infected cell. Studying the effects of phage SEpBS-1 against Salmonella infection in broiler chickens found that Salmonella counts were slightly increased at 7 and 14 days after phage treatment. However, there was no statistically significant difference between groups (p>0.05). Salmonella counts decreased by 40% at 14 days, while the positive control found the highest number of Salmonella in ceca. The application of lytic bacteriophages in the biocontrol of foodborne pathogens presents a promising approach for targeting Salmonella. Bacteriophage therapy offers an effective alternative to antibiotics for pathogen control.